Spatial-temporal reliability analysis of corroding cast iron water pipes. (December 2017) - Aryai, Vahid; Mahmoodian, Mojtaba
Abstract: Destructive effects of pipeline structural failure on the worldwide social, environmental and financial aspects reveal the importance of accurate reliability assessment of these infrastructures. In this research, the structural integrity of water cast iron pipes is assessed by a spatial-temporal reliability analysis. Random field representation is used for taking the spatial variability of corrosion depth into account. A probabilistic model for correlation length of corroded cast iron surfaces is developed using the data collected from in-service pipe samples in the West of Melbourne, Australia. To this aim, the randomness associated with involved parameters in the deterioration process is acknowledged by Monte Carlo simulation, and limit states criteria are checked for individual failure mode and also for combination of them in order to execute a multi-failure mode reliability assessment for finding the likelihood of the time of pipeline failure. Highlights: A time-dependent correlation length model has been developed. The model developed based upon the data gathered from corroded cast iron water pipes in the West of Melbourne, Australia. A multi-failure spatial-temporal reliability analysis has been performed. The methodology estimates the probability of failure of cast iron water pipes with less than 15.6% error.